IONIC LIQUID MEDIATED EXTRACTION OF BIOACTIVE COMPOUNDS FROM POLYGONUM MINUS AND THEIR APPLICATION FOR SYNTHESIS OF NANOPARTICLES - ., HABIB ULLAH (2019)

(untitled)
Ionic liquids (ILs) have become as an effective solvent for extraction of bioactive compounds from numerous plants.